Answer:
The required answer is 100 .
Step-by-step explanation:
Given function to us is ,
⇒ f(n) = 4n + 2 . And we need to find (f • f) (-3)
So , first let's find f•f , which will be ,
⇒ (f • f) = (4n + 2)(4n + 2)
⇒ (f • f) = 4n ( 4n + 2 ) +2 ( 4n + 2)
⇒ (f • f) = 16n² + 8n + 8n + 4
⇒ (f • f) = 16n² + 16n + 4
====================================
Now we need to find (f • f)(-3) . So on substituting f = (-3) , we have :-
⇒ (f • f)(n) = 16n² + 16n + 4
⇒ (f • f)(-3) = 16*(-3)² + 16*(-3) + 4
⇒ (f • f) (-3) = 16* 9 - 48 + 4
⇒ (f • f)(-3) = 144 - 44
⇒ ( f • f) (-3) = 100
<h3>
<u>Hence </u><u>the</u><u> value</u><u> of</u><u> </u><u>(</u><u> </u><u>f</u><u> </u><u>•</u><u> </u><u>f</u><u>)</u><u>(</u><u>-</u><u>3</u><u>)</u><u> </u><u>is</u><u> </u><u>1</u><u>0</u><u>0</u><u> </u><u>.</u></h3>